The effect of different essential oils on antioxidant and shelf life of traditional fermented grain beverage Turkish boza - Cakir, Elif; Kirtil, Hatice Ebrar; Arici, Muhammet (SCIENTIFIC ISSUES NATL CENTRE AGRARIAN SCIENCES, 2024)
Aromatic essential oils are used as natural preservatives due to their antibacterial properties and increased awareness of flavor, aroma and health benefits. The target was to provide new flavors and functional properties to boza, without changing the original appearance of this traditional drink. Boza samples obtained by adding sage, fennel, and ginger essential oils were compared with control boza in terms of some physicochemical features, microbiological, phenolic, antioxidant, color, and sensory properties. Boza samples were observed to have a fall in pH during 5 days of storage and the alcohol and ash values were appropriate for boza standards. The highest phenolic amounts and the greatest antioxidant activity were found in the sage and ginger boza samples, where the phenolic content was 148.11 and 122.88 mg/kg, respectively, and the antioxidant amounts were 108.6 and 96.32 mg/L, respectively. In terms of taste and aroma, the highest appreciation was seen in boza samples containing ginger on the 1st day, and boza samples containing sage on the 5th day.
Keywords: boza; essential oils; antioxidant; antimicrobial; IDENTIFICATION; BACTERIA; Environmental Sciences & Ecology